Rekayasa Peningkatan Kekerasan Permukaan Gear Sprocket Sepeda Motor dengan Metode Quenching Variasi Media Pendingin - Rauuf Nur Fattah; Sugiyanto Sugiyanto; Bambang Hari Priyambodo; Achmad Nurhidayat; Rizqi Ilmal Yaqin (Universitas Muhammadiyah Yogyakarta, 2023)
This study used an experimental research method, which is a research method that aims to understand the causal process by treatment and conducting controlled testing on a sample of research subjects. This research uses quantitative methods by taking research data in the form of numbers. The material used in this study is the gear sprocket. A gear sprocket is a motor component that transmits power from the engine to the rear wheels so that the motor can run optimally. The sprocket gear was heat treated at 850 ℃ with a holding time of 20 minutes. The variations of quenching media are mineral water, dromus coolant, and SAE 40 oil. Hardness and microstructure tests were carried out for each specimen to determine the effect of different cooling media on the quenching process. The results of this study indicate the highest specimen hardness value was obtained at 301 HV by immersion in mineral water media. The lowest hardness was obtained at 207 HV with SAE 40 oil media immersion. Meanwhile, the non-treatment material hardness is 150 HV. In this case, there was an increase in the highest hardness of about two times compared to non-treated specimens. Observation of the microstructure shows that the grain size of the mineral water quenching specimens looks smaller than that of the non-treatment models. This phenomenon supports the idea that quenching can increase the surface hardness of the gear sprocket.